Expressed sex ratio in populations of the moss Hamatocaulis vernicosus (Scorpidiaceae) in the Czech Republic with consideration of its cryptic species. - Manukjanová, Alžběta (Jihočeská univerzita, 2019)
This thesis aims at sex expression and sex ratio in cryptic species of a rare fen moss Hamatocaulis vernicosus. The sex expression and expressed sex ratio were compared at various hierarchical levels. Additionally, micromaps of expressed sex ratio in patches at 21 localities, including 5 localities where both clades co-occur have been created.
Expressed sex ratio in populations of the moss Hamatocaulis vernicosus (Scorpidiaceae) in the Czech Republic with consideration of its cryptic species.
Keywords: bryophyte; cryptic species; Hamatocaulis vernicosus; reproduction; sex ratio; bryophyte; cryptic species; Hamatocaulis vernicosus; reproduction; sex ratio